2018
DOI: 10.1371/journal.pone.0195950
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation risk comparison among ‘real-world’ newly anticoagulated atrial fibrillation patients: Apixaban, warfarin, dabigatran, or rivaroxaban

Abstract: Discontinuation of oral anticoagulants may expose non-valvular atrial fibrillation (NVAF) patients to an increased risk of stroke. This study describes the real-world discontinuation rates and compared the risk of drug discontinuation among NVAF patients initiating apixaban, warfarin, dabigatran, or rivaroxaban. This retrospective cohort study evaluated newly-anticoagulated NVAF patients in the MarketScan® data population from 01/01/2012 through 12/31/2014. Discontinuation was defined as a lack of subsequent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 23 publications
8
34
0
2
Order By: Relevance
“…In our present study, after controlling for differences in patient characteristics (such as lifestyle factors, CHA 2 DS 2- VASc Score, HAS-BLED Score and Frailty Index) between NOAC cohorts, patients starting OAC therapy on rivaroxaban had only a small increased likelihood of discontinuing treatment, while those starting on dabigatran were twice as likely to discontinue, when compared with those starting on apixaban. This is in line with findings from other studies among American and European OAC-naïve NVAF cohorts,13 15 21 but contrasts with those reported by McHorney et al 22 in USA, who found that among 23 309 patients with NVAF starting NOAC therapy, patients treated with rivaroxaban were significantly less likely to discontinue therapy at 1 year, as well as at earlier time points, compared with those starting on apixaban or dabigatran. It should be noted that the higher level of discontinuation seen for dabigatran, both in our study and in others, could be partially explained by its longer market availability.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our present study, after controlling for differences in patient characteristics (such as lifestyle factors, CHA 2 DS 2- VASc Score, HAS-BLED Score and Frailty Index) between NOAC cohorts, patients starting OAC therapy on rivaroxaban had only a small increased likelihood of discontinuing treatment, while those starting on dabigatran were twice as likely to discontinue, when compared with those starting on apixaban. This is in line with findings from other studies among American and European OAC-naïve NVAF cohorts,13 15 21 but contrasts with those reported by McHorney et al 22 in USA, who found that among 23 309 patients with NVAF starting NOAC therapy, patients treated with rivaroxaban were significantly less likely to discontinue therapy at 1 year, as well as at earlier time points, compared with those starting on apixaban or dabigatran. It should be noted that the higher level of discontinuation seen for dabigatran, both in our study and in others, could be partially explained by its longer market availability.…”
Section: Discussionsupporting
confidence: 87%
“…Studies from other European countries have reported either highly comparable,32 notably higher17 or lower15 18 1-year NOAC discontinuation rates based on a 30-day treatment gap,18 60-day treatment gap17 32 or other definition of discontinuation,15 with differences possibly attributable to differences in study size, design and/or composition of the study population (eg, the inclusion of OAC-naïve users only). One-year NOAC discontinuation rates among patient populations with NVAF reported from claims database studies in USA have been substantially higher,21 33 yet are consistent with a trend of higher discontinuation for dabigatran compared with rivaroxaban or apixaban,13 15 17 21 22 32 33 and of rates lowest for apixaban in most,13 15 17 21 33 although not all,22 studies. Most other studies on NOAC discontinuation have reported rates over shorter time periods 34…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, early discontinuation of (N)OAC treatment can be as high as 50% at 6 months in certain patient groups [18,19]. Frequently mentioned reasons for early discontinuation are (minor) bleeding, other anticoagulant-related side-effects, and a lack of the perceived need for anticoagulation [20,21]. Therefore, international guidelines recommend structured follow up of patients on NOACs (ESC) including assessment of adherence to medication, complications, interactions and regular (at least annual, but more often on indication) check on renal and liver functions [22].…”
Section: Guideline Adherence and Reasons Of Not Prescribing Anticoagumentioning
confidence: 99%
“…This risk was reduced by 30% each year thereafter based on the assumption in the STROKESTOP cost-effectiveness analysis [22]. Because real-world discontinuation rates are reportedly higher, we set the first year OAC discontinuation rate (unrelated to stroke and bleeding) to 50.5% in a scenario analysis [34]. Use of this estimate was considered to overestimate discontinuations, since the estimate does not exclude OAC discontinuations related to stroke, bleeding, myocardial infarction, and systemic embolism, which are explicitly modeled.…”
Section: Risk Of Clinical Eventsmentioning
confidence: 99%